2015
DOI: 10.1111/jcmm.12650
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA expression and its implications for diagnosis and therapy of tongue squamous cell carcinoma

Abstract: Tongue squamous cell carcinoma (TSCC) is the most common type of oral squamous cell carcinomas and is well known for its high rate of lymph nodal metastasis. Despite the identification of many molecular mechanisms in TSCC, the number of deaths associated with TSCC increased during the past 5 years. MicroRNAs (miRNAs) are a family of small non‐coding RNA molecules, which regulate gene expression by either translational inhibition or mRNA degradation. miRNAs have been proven to be key regulators of various biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 59 publications
1
49
0
Order By: Relevance
“…Emerging evidence have confirmed the important function of microRNAs in cancer development and tumorigenesis, including TSCC, acting as potent oncogenes or tumor suppressors [19]. Dysregulated micro-RNAs are also involved in the diagnosis and cure of TSCC [20]. In our study, we validated that miR-26a/ miR-26b was downregulated in TSCC tumor tissues and cells, which was similar to former reports [11,12].…”
Section: Discussionsupporting
confidence: 91%
“…Emerging evidence have confirmed the important function of microRNAs in cancer development and tumorigenesis, including TSCC, acting as potent oncogenes or tumor suppressors [19]. Dysregulated micro-RNAs are also involved in the diagnosis and cure of TSCC [20]. In our study, we validated that miR-26a/ miR-26b was downregulated in TSCC tumor tissues and cells, which was similar to former reports [11,12].…”
Section: Discussionsupporting
confidence: 91%
“…20 It is well recognized that miRNA is a post-transcriptional regulator by decreasing mRNA stability or inhibiting translation via directly targeting gene 3′-UTR. 21 In the current study, we identified that circ-CCND1 could simultaneously sponge three miR-646 to diminish the repression of miR-646 on CCND1 3′-UTR, resulting in enhancing the stability of CCND1 mRNA. Growing evidence indicates that miR-646 plays a tumour-suppressive role in a variety of human cancers, including osteosarcoma, 22 hepatocellular carcinoma 23 and gastric cancer.…”
Section: Discussionmentioning
confidence: 66%
“…The most extensively studied is circRNA as a competing endogenous RNA (ceRNA) to effectively sponge miRNA, for example, circ‐HIPK3/miR‐7 in colorectal cancer, circ‐EPSTI1/miR‐942 in ovarian cancer, circ‐ANKS1B/miR‐148/152 in breast cancer and circ‐AMOTL1L/miR‐193a‐5p in prostate cancer . It is well recognized that miRNA is a post‐transcriptional regulator by decreasing mRNA stability or inhibiting translation via directly targeting gene 3′‐UTR . In the current study, we identified that circ‐CCND1 could simultaneously sponge three miR‐646 to diminish the repression of miR‐646 on CCND1 3′‐UTR, resulting in enhancing the stability of CCND1 mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are small noncoding RNAs that can suppress the expression of protein coding genes by targeting mRNAs for cleavage and/or translational repression [13][14][15][16]. Recent evidence has demonstrated that miRNAs play critical roles in many biological processes, such as lineage determination and cell proliferation, migration, apoptosis and differentiation [2,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%